AUTISM DIAGNOSIS: COMPARISON BETWEEN PUBLIC AND PRIVATE SCHOOLS - Correa, Fernanda (2024)
This document results from a theoretical study, the objective of which was to discuss the importance of conducting high-quality diagnoses of Autism Spectrum Disorder (ASD) and to compare how this screening process is conducted through the Unified Health System (SUS) and specialized private clinics. The research was conducted through a literature review and case study analysis to assess the waiting time, cost, diagnostic quality, and follow-up care after the screening process had been completed. Autism is a neurodevelopmental condition characterized by significant deficits in communication, selective eating, and social interaction, as well as repetitive patterns of behaviors, activities, and/or interests.